Numerical seismic performance evaluation of concrete beam-column joint reinforced with different super elastic shape memory alloy rebars. (1st September 2019) - Nahar, Mumtasirun; Muntasir Billah, A.H.M.; Kamal, Habibur R.; Islam, Kamrul
Highlights: Numerical investigation of concrete beam-column joint sub-assemblage using a performance-based approach. The effect of SMA type on the performance of beam-column joints are evaluated. Performance-based damage states are developed for five different SMA-RC beam-column joints. Beam-column joints with Fe-based SMA (FeNCATB) reduced the residual deformation with improved energy dissipation. Abstract: Beam-column joint is one of the most vulnerable portions of a building during an earthquake. Sufficiently ductile materials are required to reinforce these joints so that the structure can dissipate energy and exhibit better performance during seismic events. Superelastic Shape Memory Alloys (SE SMAs) are unique materials that have the ability to undergo large inelastic deformation upon stress removal (superelasticity) or heating (shape-memory alloy effect). If such smart materials can be incorporated in the plastic hinge regions of reinforced concrete (RC) beam-column joint sub-assemblage, they can undergo large deformations without experiencing permanent deformation during an earthquake. In this context, this paper discusses the seismic performance of RC beam-column joint sub-assemblages reinforced with five different SMAs, obtained through numerical study, under reverse cyclic loading. In this study, six beam-column joint sub-assemblages, five reinforced with different types of SE SMAs, and one with regular steel, are considered. The performance of the beam-column joint sub-assemblages is numerically evaluated in terms of load-storey drift relationship, energy dissipation capacity, and cumulative energy dissipation-storey drift ratio. Nonlinear static pushover analysis is also carried out to determine the performance-based limit state for the beam-column joint sub-assemblages. The results indicate that all the SMA reinforced beam-column joint sub-assemblages have adequate energy dissipation capacity while experiencing lower residual deformation.